THE FLEXURAL STRENGTH, SURFACE HARDNESS AND SURFACE ROUGHNESS OF 3D PRINTED DENTURE BASE MATERIAL - Şahinbaş, Abdurrahman; ŞAHİNBAŞ, ABDURRAHMAN; Burduroğlu, Hatice Defne; BURDUROĞLU, HATİCE DEFNE (My University, 2019)
Keywords: 3d printing, Denture base, Surface RoughnessPurpose/Aim: The aim of this study was to evaluate the flexural strength, surface hardness and surface roughness of denture basematerials, which has produced with different production methods.Materials and Methods: Production methods to be used in this study are a conventional flasking method (Group C) N=8 and additivemanufacturing method (Group A) N=8. As an additive manufacturing method, Envisiontec Vida 3D printer and E-Denture 3D+ denturebase material (ENVISIONTEC GMBH Gladbeck, Germany) and as a conventional flasking method Meliodent® Heat Cure (KulzerGMBH Hanau, Germany) were used. Flexural strength was assessed with a three-point bending test using a universal testing machine(Shimadzu AGS-X, Columbia, Maryland). Disk specimens were subjected to surface roughness test with a profilometer (MarSurfM300C, Mahr GMBH Göttingen, Germany) and Vickers Hardness test (Shimadzu HMV, Columbia, Maryland) after finishing andpolishing procedures.Results: Mean flexural strength of Group C is 69,8N ±8,2N and Group A is 57,2N ±1,17N. Mean Ra Values of Group C is 0,065±0,027, and Group A is 0,051 ±0,02. Mean Vickers Hardness Values of Group C is 16,19 ± 0,078 and Group A is 9,9 ±0,82. For thegroup comparisons, Mann Whitney U test was used (p<0,05). There are statistical differences between groups in Vickers HardnessValues p=0,001, and in flexural strength values p=0,001. But there is no statistically differences in surface roughness levels between thegroups p=0,248.Conclusions: Additive manufacturing methods can be used to produce denture bases, but further studies are needed to use this methodsafely.